2021
DOI: 10.3390/jcm10040574
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Deficiencies in Radiotherapy-Treated Head and Neck Cancer Patients

Abstract: Nutritional deficiencies (malnutrition, cachexia, sarcopenia, and unfavorable changes in the body composition) developing as a side effect of radiotherapy (RT) currently represents a significant but still inaccurately studied clinical problem in cancer patients. The incidence of malnutrition observed in head and neck cancer (HNC) patients in oncological radiology departments can reach 80%. The presence of malnutrition, sarcopenia, and cachexia is associated with an unfavorable prognosis of the disease, higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 114 publications
0
11
0
Order By: Relevance
“…Sarcopenia – the excessive loss of skeletal muscle (SM) mass and function – is a common and debilitating phenomenon in head and neck cancer (HNC) patients ( 1 ). Weight loss is frequent in HNC due to nutritional deficiencies induced by tumor geometry affecting normal tissues ( 2 ) and/or side effects caused by therapeutic interventions ( 3 ). Although the link between treatment-associated weight loss and survival in HNC is unclear ( 4 ), sarcopenia has been strongly associated with oncologic outcomes and late radiation-induced toxicities ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Sarcopenia – the excessive loss of skeletal muscle (SM) mass and function – is a common and debilitating phenomenon in head and neck cancer (HNC) patients ( 1 ). Weight loss is frequent in HNC due to nutritional deficiencies induced by tumor geometry affecting normal tissues ( 2 ) and/or side effects caused by therapeutic interventions ( 3 ). Although the link between treatment-associated weight loss and survival in HNC is unclear ( 4 ), sarcopenia has been strongly associated with oncologic outcomes and late radiation-induced toxicities ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the current evidence on the impact of SP in patients undergoing RT comes from analyses on patients with head and neck tumors [ 5 , 59 ]. However, several studies reported a significantly negative impact of SP on overall survival not only in patients undergoing RT for head and neck cancers [ 25 , 60 , 61 , 62 , 63 ], but also in the esophagus [ 64 ], rectum [ 65 ], pancreas [ 66 ], cervix [ 67 ], and lung [ 68 ] tumors.…”
Section: Impact Of Sarcopeniamentioning
confidence: 99%
“…The mechanisms underlying the progression of malnutrition in patients with LAHNSCC can be attributed to inadequate energy intake and aberrant metabolism caused by varied degrees of systemic inflammation induced by cancer, treatment, or both [ 6 , 13 , 14 ]. The provision of sufficient energy intake and restriction of systemic inflammation are essential and reasonable approaches to prevent the development of malnutrition [ 4 ].…”
Section: Introductionmentioning
confidence: 99%